2020
DOI: 10.3390/app10041499
|View full text |Cite
|
Sign up to set email alerts
|

Growing Biofuel Feedstocks in Copper-Contaminated Soils of a Former Superfund Site

Abstract: Copper mining in the Upper Peninsula of Michigan in the mid-19th century generated millions of tons of mining waste, called stamp sand, which was deposited into various offshoots of Lake Superior. The toxic stamp sand converted the area into barren, fallow land. Without a vegetative cover, stamp sand has been eroding into the lakes, adversely affecting aquatic life. Our objective was to perform a greenhouse study, to grow cold-tolerant oilseed crops camelina (Camelina sativa) and field pennycress (Thlaspi arve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Phytomanagement can provide financial benefits through planting valuable crops that serve as feedstock for multiple industries and end-products such as furniture, pulp and paper, biochemicals (adhesives and detergents), insulation and building materials, composites and plastic alternatives, food additives, animal feeding and bedding, etc. Some of these crops can also be used as bioenergy crops yielding high-quality biomass (Nsanganwimana et al, 2014(Nsanganwimana et al, , 2015Burges et al, 2018;Lacalle et al, 2018;Mench et al, 2018;Thijs et al, 2018) to produce renewable energy (electricity, heat and biofuels) (Gonsalvesh et al, 2016;Pandey et al, 2016;Rizwan et al, 2018;Grottola et al, 2019;Pogrzeba et al, 2019;Rusinowski et al, 2019;Sidhu et al, 2020;Tran et al, 2020 ). Most importantly, these crops offer the possibility to combine the production of biomass for energy production and/or other end-products (Grisan et al, 2016;Barla and Kumar, 2019) with TE phytoextraction or phytostabilization (Thijs et al, 2018;Chalot et al, 2020).…”
Section: Phytomanagement Benefits and Constraints-brief Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytomanagement can provide financial benefits through planting valuable crops that serve as feedstock for multiple industries and end-products such as furniture, pulp and paper, biochemicals (adhesives and detergents), insulation and building materials, composites and plastic alternatives, food additives, animal feeding and bedding, etc. Some of these crops can also be used as bioenergy crops yielding high-quality biomass (Nsanganwimana et al, 2014(Nsanganwimana et al, , 2015Burges et al, 2018;Lacalle et al, 2018;Mench et al, 2018;Thijs et al, 2018) to produce renewable energy (electricity, heat and biofuels) (Gonsalvesh et al, 2016;Pandey et al, 2016;Rizwan et al, 2018;Grottola et al, 2019;Pogrzeba et al, 2019;Rusinowski et al, 2019;Sidhu et al, 2020;Tran et al, 2020 ). Most importantly, these crops offer the possibility to combine the production of biomass for energy production and/or other end-products (Grisan et al, 2016;Barla and Kumar, 2019) with TE phytoextraction or phytostabilization (Thijs et al, 2018;Chalot et al, 2020).…”
Section: Phytomanagement Benefits and Constraints-brief Overviewmentioning
confidence: 99%
“…In the past 10-15 years, some energy crops have arisen as most promising in adding value to TE-contaminated areas by generating biomass-based products (gaseous, liquid, and solid) (Grzegórska et al, 2020) that can be converted into different kinds of energy (heat, electricity, and fuel for transportation), while attaining environmental goals. Other industrial crops (e.g., fiber crops), aromatic plants, ornamental plants and biofortified crops are also perfectly suitable for phytomanagement, as one of the commitments of this phytotechnology is to deliver economic benefits for the endusers (Gonsalvesh et al, 2016;Pandey et al, 2016;Rizwan et al, 2018;Grottola et al, 2019;Sidhu et al, 2020).…”
Section: Plant Selectionmentioning
confidence: 99%
“…Such a cultivation may be located in worse environmental conditions and in fallow areas. Sidhu et al [13] reported that the advantage of camelina is its beneficial effect on the natural environment; for example, reduction of soil erosion. Załuski et al [14] have concluded that the observed climate changes result in the search for species that can be cultivated in less favorable environmental conditions and camelina has been indicated as one of such plants.…”
Section: Introductionmentioning
confidence: 99%